Distribution of CYP2C8 and CYP2C9 amino acid substitution alleles in South Indian diabetes patients: A genotypic and computational protein phenotype study. (20th September 2017) - Rao, Durga Koteswara; Murthy, Dwaraknath K; Shaik, Nazia Sultana; Banaganapalli, Babajan; Konda, Kumaraswami; Rao, Hanmantha P; Ganti, Eswar; Ahmed Awan, Zuhair; A El‐Harouni, Ashraf; Elango, Ramu; Ali Khan, Imran; Shaik, Noor Ahmad
Summary: The CYP2C8 and CYP2C9 are two major isoforms of the cytochrome P450 enzyme family, which is involved in drug response, detoxification, and disease development. This study describes the differential distribution of amino acid substitution variants of CYP2C8 (*2‐I269F & *3‐R139K) and CYP2C9 (*2‐C144R & *3‐L359A) genes in 234 type 2 diabetes mellitus (T2DM) patients and 218 healthy controls from Andhra Pradesh, South India. Single locus genotype analysis has revealed that homozygous recessive genotypes of 2C8*2‐TT ( P  ≤ .03), 2C9*2‐TT ( P  ≤ .02), and heterozygous 2C9*3‐AC ( P  ≤ .006) are seen to be increasingly present in the case group, indicating a significant level of their association with diabetes in Andhra population. The statistical significance of these recessive genotypes has persisted even under their corresponding allelic forms ( P  ≤ .01). Genotype association results were further examined by computational protein structure and stability analysis to assess the deleteriousness of the amino acid changes. The mutant CYP 2C8 and 2C9 (both *2 and *3) proteins showed structural drifts at both amino acid residue (range 0.43Å‐0.77Å), and polypeptide chain levels (range 0.68Å‐1.81Å) compared to their wild‐type counterparts. Furthermore, the free energy value differences (range –0.915 to –1.38 Kcal/mol) between mutant and native protein structures suggests the deleterious and destabilizing potential of amino acid substitution polymorphisms of CYP genes. The present study confirms the variable distribution of CYP2C8 (*2 and *3) and CYP2C9 (*2 and *3) allelic polymorphisms among South Indian diabetic populations and further warrants the serious attention of CYP gene family, as a putative locus for disease risk assessment and therapy.